2015
DOI: 10.1017/s000711451500149x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary enterolactone associated with liver enzyme levels in US adults: National Health and Nutrition Examination Survey (NHANES)

Abstract: Phyto-oestrogens are a family of plant-derived xeno-oestrogens that appear to have beneficial effects on human health. To date, no data are available about phyto-oestrogen consumption affecting liver health in a population. The present study aimed to explore the relationship of urinary phyto-oestrogen metabolites with serum liver enzymes in US adults. A nationally representative sample of US adults in the National Health and Nutrition Examination Survey (NHANES) 2003 -10 was analysed. The cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Metabolites may also be associated with signaling pathways related to the development of cancer, and therefore can serve as predictors of disease. 24 Enterolignans, which eventually undergo enterohepatic circulation, may affect metabolic pathways by regulating sterol transporters 25 , steroid hormones and their receptors 26, 27 , and liver enzymes 28 . Hence, it is possible that enterolignans alter plasma metabolite abundances as a result of their activity on various tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolites may also be associated with signaling pathways related to the development of cancer, and therefore can serve as predictors of disease. 24 Enterolignans, which eventually undergo enterohepatic circulation, may affect metabolic pathways by regulating sterol transporters 25 , steroid hormones and their receptors 26, 27 , and liver enzymes 28 . Hence, it is possible that enterolignans alter plasma metabolite abundances as a result of their activity on various tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 5 years, additional observational studies looking at urinary enterolactone or enterodiol have been published using NHANES data, which is a nationally representative sample of the U.S. population. Studies evaluated different classifications of urinary enterolignans and populations . The results from NHANES studies support that urinary enterolactone and enterodiol are associated with more favorable cardiometabolic risk factors, including BMI, abdominal obesity, triglycerides, HDL cholesterol, blood pressure, and inflammation, and that associations appear stronger for enterolactone.…”
Section: Other Phytoestrogensmentioning
confidence: 86%
“…In the last 5 years, additional observational studies looking at urinary enterolactone or enterodiol have been published using NHANES data, which is a nationally representative sample of the U.S. population. Studies evaluated different classifications of urinary enterolignans and populations [119][120][121][122][123].…”
Section: Other Phytoestrogensmentioning
confidence: 99%
“…Decreased urinary enterolactone concentrations as observed in high ultra-processed food consumers may have serious health consequences if, as was shown in a study carried out with US NHANES 2003–2010 survey, urinary enterolactone concentrations are inversely associated with serum g-glutamyl transaminase (GGT) levels in adult males and females, with alkaline phosphatase (ALP) in females, and with aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels in adult males as well [63]. Also, another study carried with US NHANES 2001–2010, found an inverse association between urinary enterolactone levels and obesity, waist circumference, serum triacylglycerols (TAG) levels, fasting glucose levels, fasting insulin levels and metabolic syndrome in adult males, and a direct association with high-density lipoprotein HDL-cholesterol levels [64].…”
Section: Discussionmentioning
confidence: 99%